Causality between multiple autoimmune disorders and migraine and its subtypes: a two-sample Mendelian randomization study - Li, Rui; Han, Jing; Shao, Guoliang; Liu, Changyue; Li, Shuo; Wang, Mengmeng; Yang, Dianhui (Frontiers in Neurology, 2024)
Introduction Several studies have reported associations between various autoimmune diseases and migraine. Using Mendelian randomization (MR), this study aimed to evaluate the interplay between autoimmune diseases and migraine. Methods Here, instrumental variables, exposure factors, and outcome factors for 10 common autoimmune diseases and migraine and its subtypes were screened. This screening utilized comprehensive statistics from Europe’s largest genome-wide association study and performed reverse MR analysis on positive results. The causality between autoimmune diseases and migraine was comprehensively assessed using multiple analytical methods. Additionally, sensitivity analyses, such as the horizontal diversity heterogeneity and leave-one-out method, were performed. Results Random-effects inverse variance weighting analysis revealed a causal correlation between autoimmune hyperthyroidism and migraine (p = 0.0002), and this association was consistent across both migraine with aura (MA; p = 0.006) and migraine without aura (MO; p = 0.017). In addition, there was a positive causal association between systemic lupus erythematosus (SLE) and MA (p = 0.001) and between hypothyroidism and MO (p = 0.038). There is insufficient evidence to substantiate a causal link between outcomes and other autoimmune-related disorders, and reverse MR results did not reveal a causal relationship between migraines and these autoimmune disorders. The validity of the results was demonstrated by a sensitivity analysis; horizontal pleiotropy and heterogeneity were not observed. Discussion This study observed a positive genetic association between autoimmune hyperthyroidism and migraines. In addition, SLE positively affects MA, and hypothyroidism contributes to the incidence of MO. These results have great significance for future research and prevention of migraine.